Analisa Penambahan Dinding Geser pada Gedung dengan Ketidakberaturan Vertikal 1a dan 1b akibat Beban Gempa - Muhammad Arie Farkhan; Wahyu Kartini; Cintantya Budi Casita (KERN, 2022)
The performance of a building is greatly affected by the configuration of the building's structure when it is hit by an earthquake. Structures are divided into two types, namely regular structures and irregular building structures. The irregular configuration of the building structure can worsen the safety of the building when it is hit by an earthquake. Therefore, the building structure needs to be strengthened in order to minimize the occurrence of collapse due to the earthquake. Shear walls are an option for strengthening structures in earthquake-prone areas. The structural system used is a dual system where the combination of the moment resisting frame system and the structural wall is used. In the analysis of the dual system, two types of shear wall placement are used. Shear wall as a single wall with a location on the exterior of the building at the corner and center of the building. In this study used dynamic response analysis with the Surabaya earthquake area. The results show that shear walls are able to increase the stiffness of the building and make buildings with vertical irregularities level 1a and 1b avoidable.